Justice, Institutions, and Society: Cross-Cultural Analysis of Prosecution Systems - Pamungkas, Agung; Faishal, Achmad; Tornado, Anang Shophan (DIKTUM: Jurnal Syariah dan Hukum, 2025)
Background: Comparative scholarship on prosecution systems often emphasizes structural and procedural distinctions between adversarial, inquisitorial, and mixed models, yet it rarely engages with how prosecutorial practices are shaped by socio-cultural norms and moral frameworks in real-world contexts . Purpose: This study aims to critically examine international prosecution models through an anthropological fiqh lens, analyzing how prosecutorial discretion, independence, and accountability are influenced not only by institutional design but also by religious values, local ‘urf, and communal ethics. Methods: The research employs a comparative socio-legal methodology that combines document analysis, semi-structured interviews with prosecutors and legal practitioners, and ethnographic observation in selected jurisdictions, including both civil law and common law traditions, as well as Muslim-majority legal systems. Findings: Results indicate that while formal structures prioritize legal certainty and efficiency, prosecutorial decision-making is frequently mediated by moral considerations and socio-cultural legitimacy. These dynamics generate significant variations in outcomes across jurisdictions, particularly in cases involving restorative justice, diversion, or sensitive moral offenses . Theoretical and Practical Implications: the study bridges legal philosophy with empirical practice, offering new insights into how prosecution systems can balance codified law with communal notions of justice. The findings also provide practical guidance for legal reforms aimed at enhancing prosecutorial transparency and fairness. Originality/Novelty: This research advances comparative prosecution studies by integrating anthropological fiqh into empirical analysis, producing a culturally grounded framework that reconceptualizes prosecutorial discretion within global criminal justice systems